HER+ Multidimensional Gender Norms Index in Agri-food Systems - Costenbader, Betsy (FHI 360, 2023)
Gender inequalities remain deeply entrenched in many agri-food systems (AFS), limiting the potential of women—especially those from agriculture-dependent communities—to be empowered and to build social and economic resilience to climate change challenges. The Harnessing Gender and Social Equality for Resilience in Agri-food Systems (HER+) initiative will generate learning and evidence on where and how to intervene at a deeper level to disrupt the foundations of inequality in AFS. This effort requires high-quality data. Yet, currently no tool exists to measure and track gender and social norms in AFS and how norms may differ across AFS, geographical regions, or actor groups performing different roles in the AFS. This work supports HER+ through the development of a survey-based tool to measure the perceptions of women and men working in AFS toward inequitable social and gender norms and, ultimately, to assess the level of gender bias within and across three AFS: cassava, fish and chicken. This presentation will cover the development process of the tool from local stakeholder consultations to the cognitive testing and piloting of the tool in Tanzania and Nigeria. We will present preliminary evidence from these pilot studies and make recommendations for how the tool could be used and adapted by researchers and development organizations working in other agricultural contexts. These findings will, in turn, inform the design of gendertransformative approaches to address harmful social and gender norms in the three AFS.